2013
DOI: 10.1590/1516-3180.2013.1316523
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplant anemia and associated risk factors: the impact of steroid-free therapy

Abstract: CONTEXT AND OBJECTIVE: The prevalence of post-renal transplant anemia (PTA) reported in the literature is variable and several factors contribute towards its pathophysiology. This study aimed to investigate the prevalence of PTA, its associated risk factors and the impact of therapy without steroids. DESIGN AND SETTING: Retrospective cohort study in a renal transplantation unit at a tertiary hospital. METHODS: Anemia was defined as hemoglobin (Hb) < 12 g/dl in female adult recipients and < 13 g/dl in males. Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Infection with parvovirus B19 must be strongly suspected when refractory and severe anemia with reticulocytopenia develops after transplantation ( 61 ). Studies have also shown that avoiding the use of steroids in the first 6 months after kidney transplantation also increases the incidence of PTA ( 62 ). Acute kidney injury and nutritional deficiencies are also important influencing factors for early PTA ( 5 ).…”
Section: Risk Factors For the Occurrence Of Ptamentioning
confidence: 99%
See 1 more Smart Citation
“…Infection with parvovirus B19 must be strongly suspected when refractory and severe anemia with reticulocytopenia develops after transplantation ( 61 ). Studies have also shown that avoiding the use of steroids in the first 6 months after kidney transplantation also increases the incidence of PTA ( 62 ). Acute kidney injury and nutritional deficiencies are also important influencing factors for early PTA ( 5 ).…”
Section: Risk Factors For the Occurrence Of Ptamentioning
confidence: 99%
“…The onset of late PTA is associated with impaired kidney graft function and the development of renal insufficiency ( 63 ). Delayed graft function, impaired kidney graft function, and acute rejection are risk factors for PTA ( 62 ). Serum creatinine and glomerular filtration rates have been shown to affect Hb in patients ( 20 ).…”
Section: Risk Factors For the Occurrence Of Ptamentioning
confidence: 99%